Studies on the gene regulatory networks that control sporulation initiation in Clostridioides difficile - Adhikari Dhungel, Babita (Kansas State University, 2020)
Clostridioides difficile is a Gram-positive, spore-forming anaerobic bacillus and is the causative agent of C. difficile Infection (CDI). CDI is the consequence of antibiotic therapy, which disrupts the commensal gut microbiota, thus providing a favorable environment for an opportunistic pathogen like C. difficile to outgrow and cause infection. Clostridioides difficile produces toxins A & B, that damage host epithelial cells leading to diarrheal symptoms. Clostridioides difficile also produces metabolically dormant spores that are resistant to antibiotics and detergents and are the major cause of transmission and persistence of the disease. Hyper- sporulation observed in the strains that emerged in the early 2000s is attributed to their higher transmission rates and, hence, increased CDI incidence in Europe and North America. Sporulation pathways are poorly characterized in C. difficile and the mechanism by which sporulation initiation occurs in this pathogen is not well understood. Here, I present data from two different studies on C. difficile sporulation. In our first study, we determined the regulatory relationship between Spo0A, the sporulation master regulator with SinR, a pleiotropic regulator in C. difficile. By using genetic and biochemical approaches, we demonstrated that Spo0A directly binds to the upstream of sin locus and represses the expression of sinR. In the second part of the study, we identified the novel link between intracellular c-di-GMP concentration and sporulation. We found that the upregulation of pdcB coding for a phosphodiesterase reduces the intracellular concentration of c-di-GMP. This change in the level of c-di-GMP positively influenced sporulation in C. difficile UK1 strain. By showing that a DNA inversion regulates pdcB gene expression, we have discovered the phase variable regulation of intracellular c-di-GMP concentration. Additionally, by finding that CodY, a global nutritional regulator, binds to and represses the expression of pdcB, we redefined CodY mediated gene regulatory networks of sporulation initiation in C. difficile. Together, findings from our studies have added new players and links in the gene regulatory network of C. difficile sporulation.
Keywords: Clostridioides difficile; c-di-GMP; Phosphodiesterase; Sporulation; sinR; Spo0A